Evaluation of cannibalistic cells: a novel entity in prediction of aggressive nature of oral squamous cell carcinoma. (August 2013) - Jose, Deepa; Mane, Deepa R; Datar, Uma; Muttagi, Sidhramesh; Hallikerimath, Seema; Kale, Alka D
Abstract Objective. Cellular cannibalism is a distinctive morphologic feature exclusively seen in aggressive malignancies and is defined as a large cell enclosing a slightly smaller one within its cytoplasm. This phenomenon has been illustrated in several malignancies and is correlated well with the degree of anaplasia, invasive and metastatic potential of tumor cells. However, this marker has not been extensively studied and is often unnoticed during the routine histopathological assessment of Oral squamous cell carcinoma (OSCC). Thus, the aim of this research was to evaluate the presence of cannibalistic cells (CC) and to find if there exists any association with the aggressive nature of OSCC. Materials and methods: In total, 20 neck dissection cases of OSCC with follow-up data were included in the study. The cannibalistic cells were evaluated in the lesion tissues. Cellularity of cannibalism is graded asGrade I: < 5 cells, Grade II: 6–15 cells and Grade III:> 16 cells. The data was analyzed using Fischer Exact test. Results. Out of 20 cases, all the cases showed presence of CC, Grade I in five cases, Grade II in eight cases and Grade III in seven cases. A statistically significant relation between advanced grade of cellular cannibalism and lymph node positive status (p≤ 0.001) was obtained. Conclusion. Interestingly the cases with positive lymph node metastasis demonstrated Grade 3 CC.Hence, during routine histopathological examination, the search of CC can be considered as one of the important parameters to note the aggressive nature of OSCC.